Teacher’s Techniques in Teaching Reading Narrative Text to the Eighth Grade Students of UPTD SMP N 5 Pematang Siantar - Situmorang, Abisag Rinayati; Napitupulu, Selviana; Sitanggang, Anita (CV. Tripe Konsultan, 2024)
This research aims to explore the various techniques employed by English teachers in teaching reading comprehension of narrative texts to eighth-grade students at UPTD SMP N5 Pematang Siantar. The participants in this research were eighth-grade English teachers at UPTD SMP N5 Pematang Siantar. The data were collected from various sources, including classroom observations, interviews, and analysis of teaching materials such as syllabi, textbooks, and lesson plans. The researcher employed a descriptive qualitative research approach. The data was meticulously analyzed, focusing on the teacher’s technique. The findings of this research revealed that teachers frequently used the technique of translating literature passages and employing question-and-answer exercises. This technique enables students to comprehend the content of the reading material, acquire information from the text, and enhance their critical thinking skills through direct engagement with the questions and answers.